Artefatos da contabilidade gerencial: um estudo no consórcio Alumar - Soares, Francisco Moreira (2010)
The social, economical, political and technological changes headed by globalization, the organizations development that characterize the contemporary world, led to a rethink of its organizational conducts in a way to find new standards, products and processes that contribute to the corporate efficiency and the sustainability of the companies. By using evolutionary stages of managerial accounting and its tools, divulged by Institute of Management of Accounting – IMA (1989) in the decade of 80, Soutes and De Zen (2005), classified these tools in two blocks: the traditional, represented by stages I and II tools; and the modern, that puts together stages II and IV tools. The main objective of this research is to identify the use of these tools in Consortium and its members, which fit stages III and IV, in accordance with Institute of Management of Accounting – IMA (1989) research and considered modern tools by Soutes and De Zen (2005). It is a research of descriptive basis, with a qualitative approach, by using documental bibliography and investigative technique named study case taking as analysis unit Consórcio de Alumínio do Maranhão – ALUMAR and its members: Alcoa Alumínio S/A, BHPBilliton S/A, RioTintoAlcan Ltda and Alcoa World Alumina S/A. Questionnaires were applied to professional managers that somehow are able to identify, use or realize use of managerial accounting tools at the analyzed institution management. Interviews with controllers of the consortium and its members were performed. The literature revision highlights results gotten by other researches, which were compared to the outcome acquired by present dissertation. The research demonstrated that the companies object of the study case apply CG tools, the degree of importance of each one and the frequency of use, among the tools, there was no identification of use for GECON or transfer price. The tools used by consorcio Alumar are usually the same used by companies that make up a consortium, mainly that leads or manage the consortium, influence the definition of the tools used by the consortium. It was highlighted that the consortium and its members use CG tools to assist managers in decision making at the companies management at all phases and to add value to the ones interested in accounting information.